Mutations in ERGIC1 cause Arthrogryposis multiplex congenita, neuropathic type. Issue 1 (26th July 2017) - Reinstein, E.; Drasinover, V.; Lotan, R.; Gal‐Tanamy, M.; Bolocan Nachman, I.; Eyal, E.; Jaber, L.; Magal, N.; Shohat, M.
Abstract : Arthrogryposis multiplex congenita (AMC) is heterogeneous group of disorders characterized by non‐progressive joint contractures from birth that involve more than 1 part of the body. There are various etiologies for AMC including genetic and environmental depends on the specific type, however, for most types, the cause is not fully understood. We previously reported large Israeli Arab kindred consisting of 16 patients affected with AMC neuropathic type, and mapped the locus to a 5.5 cM interval on chromosome 5qter. Using whole exome sequencing, we have now identified homozygous pathogenic variant in the ERGIC1 gene within the previously defined linked region. ERGIC1 encodes a cycling membrane protein which has a possible role in transport between endoplasmic reticulum and Golgi. We further show that this mutation was absent in more than 200 samples of healthy unrelated individuals of the Israeli Arab population. Thus, our findings expand the spectrum of hereditary AMC and suggest that abnormalities in protein trafficking may underlie AMC‐related disorders. Abstract :